There’s No Place Like Home: Importance of Housing Stability for Reentry - Reece, Beverly (American journal of criminal justice, 2023)
Research suggests a number of barriers to successful reentry for justice-involved individuals, even after a short period of detention in jail. The challenges are well-documented, with housing being one of the most salient needs returning citizens face (Lutze et al., 2014; O’Brien, 2001; Roman and Travis, 2004). Estimates of housing instability and homelessness vary widely (Metraux & Culhane, 2006; Schlay & Rossi, 1992) as those incarcerated and those who are homeless are considered "hard-to-reach" populations (Umamaheswar, 2018). This is important as housing instability can have direct consequences for reoffending behavior, and stable housing has been shown to reduce recidivism (Bobashev et al., 2009; Lutze et al., 2014; Metraux & Culhane, 2004; Steiner et al., 2015). The current study employs a unique sample of male and female inmates in a jail reentry program to examine the prevalence of housing instability and the circumstances that led to said housing issues. This study fills a gap in the previous literature by making a distinction among those who are more stably housed, precariously housed, and literally homeless. We discuss the consequences of housing instability as well as important policy implications for this population.